ANALISIS KAUSALITAS TEKNOLOGI INFORMASI KOMUNIKASI (TIK) DAN PERTUMBUHAN EKONOMI DI ASEAN - Sahrina Sahrina; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study examined the causal relationship between fixed telephone subscriptions, mobile cellular subscriptions, fixed broadband subscriptions, internet users and economic growth using a panel vector autoregrassion model (PVAR) for ASEAN’s five founding countries in the period of 2001-2015. The results of this study showed that are there is no causality between Fixed Telephone subcription and economic growth, an  unidirectional relationship between mobile celluler subscriptions and economic growth where is that just economic growth gives influence to mobile cellular subscriptions, an unidirectional relationship between fixed broadband subscription and economic growth where is that just fixed broadband subscriptions gives influence to economic growth and an unidirectional relationship from economic growth to internet users where is that just economic growth gives influence to mobile cellular subscriptions.